Crystal structure of the anticancer drug carmustine determined by X-ray powder diffraction. Issue 3 (September 2021) - Schlesinger, Carina; Alig, Edith; Schmidt, Martin U.
Abstract : The structure of the anticancer drug carmustine (1, 3-bis(2-chloroethyl)-1-nitrosourea, C5 H9 Cl2 N3 O2 ) was successfully determined from laboratory X-ray powder diffraction data recorded at 278 K and at 153 K. Carmustine crystallizes in the orthorhombic space group P 21 21 21 with Z = 4. The lattice parameters are a = 19.6935(2) Å, b = 9.8338(14) Å, c = 4.63542(6) Å, V = 897.71(2) Å³ at 153 K, and a = 19.8522(2) Å, b = 9.8843(15) Å, c = 4.69793(6) Å, V = 921.85(2) Å³ at 278 K. The Rietveld fits are very good, with low R -values and smooth difference curves of calculated and experimental powder data. The molecules form a one-dimensional hydrogen bond pattern. At room temperature, the investigated commercial sample of carmustine was amorphous.